2019
DOI: 10.11591/ijeecs.v15.i2.pp697-703
|View full text |Cite
|
Sign up to set email alerts
|

Channel length scaling and electrical characterization of graphene field effect transistor (GFET)

Abstract: <p>The exclusive monoatomic framework of graphene makes it as an alluring material to be implemented in electronic devices. Thus, using graphene as charge carrying conducting channel material in Field Effect Transistors (FET) expedites the opportunities for production of ultrasensitive biosensors for future device applications. However, performance of GFET is influenced by various parameters, particularly by the length of conducting channel. Therefore, in this study we have investigated channel length sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The incorporation of 2D nanomaterials, especially carbon-based nanomaterials, as the transducing channel material elevates the sensitivity of a sensing platform to its surrounding charges. Hence, the use of the GFET device developed by our group for ultra-sensitive detection is proposed for the detection of these infection-mediated clinical biomarkers [ 107 , 108 ]. This optimized single-layer graphene-based sensing platform exhibited an LOD of as low as ag/mL ( ) and a linear detection range from pg/mL to mg/mL for the effective sensing of anti-diuretic hormone.…”
Section: Insights Into Infection-mediated Clinical Biomarkers and Their Electrical Biosensors In Covid-19 Electrical Biosensing Platformsmentioning
confidence: 99%
“…The incorporation of 2D nanomaterials, especially carbon-based nanomaterials, as the transducing channel material elevates the sensitivity of a sensing platform to its surrounding charges. Hence, the use of the GFET device developed by our group for ultra-sensitive detection is proposed for the detection of these infection-mediated clinical biomarkers [ 107 , 108 ]. This optimized single-layer graphene-based sensing platform exhibited an LOD of as low as ag/mL ( ) and a linear detection range from pg/mL to mg/mL for the effective sensing of anti-diuretic hormone.…”
Section: Insights Into Infection-mediated Clinical Biomarkers and Their Electrical Biosensors In Covid-19 Electrical Biosensing Platformsmentioning
confidence: 99%
“…Furthermore, synthesis of nanocomposites of rGO with n-type metal oxides improves the homogeneity of the material deposited in the channel, resulting in better conductivity of the FET [ 16 ]. The most important factor to determine a more sensitive biosensor is the optimisation of the nanostructures appropriate to the transducing material, where many researchers have devoted their time [ 3 , 14 , 17 ] Kobayashi et al suggested that in order to enhance the performance of rGO-metal oxide devices, it is critical to model and understand the electrical conduction process [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wrapped capacitor there are many information about the charge and the voltage of the capacitor [7]- [11]. The capacitor can be divided into two types that is the polar capacitor and the nonpolar capacitor [12], [13]. There are several kinds of capacitor that is mylar, ELCO and ceramic [14], [15].…”
Section: Introductionmentioning
confidence: 99%